PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN TRIGONOMETRI DI KELAS XI MIPA 1 SMA NEGERI 2 PEKANBARU: Application of Active Learning Strategy Learning Tournament Type to Increase Learning Learning Results on Trigonometry Subject Class XI MIPA 1 SMA Negeri 2 Pekanbaru - Masril Masril (Perspektif Pendidikan dan Keguruan, 2017)
Learning is a process that contains a series of actions of teachers and learners on the basis of reciprocal relationships that take place in educational situations to achieve learning objectives. The science of mathematics is a natural science that studies about the science of measuring the certain. A person who studies mathematics requires not only skill, but also a thought process for understanding, discovering, developing concepts, theories and laws and solving problems in everyday life.Subjects in the subjects of mathematics are required understanding, analysis and ability of learners to link learning in everyday life. One of the materials learned in mathematics learning is trigonometry, therefore teachers are expected to develop the creativity of learners in learning.This is because creativity is able to interpret abstract concepts by involving curiosity, the ability to discover, explore, express ideas and feelings Learning Tournament is a technique that combines a group of learning and team competitions, and can be used to develop lessons on a wide variety of facts, concepts, and expertise. The presence of tournaments or matches every learner wants to get good grades, both individual desires and group desires.Therefore, learners who have weak skills are expected to be motivated to learn, in order to win the game and learners who have more ability, feel the need to share knowledge with learners who are less clever to get a high score and win the game. Based on the result of research, the value of first cycle, second cycle and third cycle in a row (76,76%), (79,11%) and (85,29%).